AB0241 PREVALENCE OF ANXIOUS SYMPTOMS AND DEPRESSION IN A SAMPLE OF PATIENTS WITH RHEUMATOID ARTHRITIS (RA) AND OTHER CHRONIC RHEUMATIC DISEASES. (2nd June 2020) - Crepaldi, G.; Voci, M.; Saracco, M.; Laezza, A.; Santino, P.; Marcato, M.; Rovera, G.; Lomater, C.
Abstract : Background: Clinical practice with patients suffering from chronic diseases highlights the presence of psychological symptoms of discomfort fed by biological and non-biological mechanisms linked to disease and treatment. In rheumatic diseases, literature detects the presence of anxious symptoms and depressed mood of clinical and sub-clinical importance with a multifactorial genesis 1 . Objectives: To detect the impact on the state of health of anxious symptoms and depressed mood in a population suffering from RA and other rheumatic diseases in order to implement the effectiveness of psychological intervention through the selection of patients who present critical levels of discomfort. Methods: Patients afferent to the Rheumatology outpatient clinic of Mauriziano Hospital have been screened from May 2018 to July 2018 with two self-administered questionnaires: HADS-A and HADS-D (Hospital Anxiety and Depression Scale), specifically developed for the evaluation of anxious and depressive symptoms in medical pathologies, and HAQ (Health Assessment Questionnaire) to explore functional disability. Data about rheumatic diagnosis and socio-demographic characteristics were also collected. Data were analyzed with descriptive statistics; the Student Test and the ANOVA test were used to evaluate prevalence and to compare the presentation of symptoms in the different diseases and the Pearson correlation coefficient was used to evaluate the relationship between symptoms and disability. Results: A total of 427 subjects were screened (317 females and 110 males), aged between 19 and 90 years (mean 60 ± 14 yrs). 156 subjects (36.5%) had a diagnosis of RA, 76 (17.8%) of psoriatic arthritis, 42 (9.8%) of ankylosing spondylitis, 14 (3.3%) of systemic lupus erythematosus and 139 (32.6%) of other rheumatic diseases (including Sjogren, osteoarthritis, fibromyalgia). A high prevalence of anxious symptoms and depressed mood has been found and the number of subjects reporting scores indicating a clinically relevant uncomfortable situation (HADS ≥ 11) was also relevant (Table 1 ); an increased prevalence in female patients was observed. There were no differences in the presentation of symptoms between RA and the other included pathologies (Table 2 ). There was a positive and significant correlation between anxious symptoms or depressed mood and functional disability (0.49 and 0.60 respectively, p<0, 01). Conclusion: The results show a significant presence of uncomfortable situations that could evolve in a psychopathological sense. The discomfort expressed through anxious and depressive symptoms is related to the level of functional disability. Recognizing the presence of psychological distress allows to orient the treatment plan and facilitate the patient's adaptation to the disease condition. References: [1]Geenen R. et al. Best Pract Res Clin Rheumatol. 2012;26(3):305-19. Disclosure of Interests: Gloria Crepaldi Consultant of: Advisory board for Sanofi and Celgene, Speakers bureau: BMS, MSD, Mariarosaria Voci: None declared, Marta Saracco: None declared, Antonella Laezza: None declared, Paolo Santino: None declared, Maddalena Marcato: None declared, Guido Rovera: None declared, Claudia Lomater Consultant of: Advisory board for Sanofi, Novartis, Abbvie